The Relationship Between Plant-Based Diet and Risk of Digestive System Cancers: A Meta-Analysis Based on 3,059,009 Subjects - Zhao, Yujie; Zhan, Junyi; Wang, Yongsen; Wang, Dongli (Frontiers in Public Health, 2022)
ABSTRACT Background and Objectives: Diets containing red or processed meat are associated with a growing risk of digestive system cancers. Whether a plant-based diet is protective against cancer needs a high level of statistical evidence. Methods: We performed a meta-analysis of five English databases, including PubMed, Medline, Embase, Web of Science databases, and Scopus, on October 24, 2021 to identify published papers. Cohort studies or case-control studies that reported a relationship between plant-based diets and cancers of the digestive system were included. Summary effect-size estimates are expressed as Risk ratios (RRs) or Odds ratios (ORs) with 95% confidence intervals and were evaluated using random-effect models. The inconsistency index (I2) and τ2 (Tau2) index were used to quantify the magnitude of heterogeneity derived from the random-effects Mantel-Haenszel model. Results: The same results were found in cohort (adjusted RR=0.82, 95% CI: 0.78-0.86, P <.001, I2=46.4%, Tau2=0.017) and case-control (adjusted OR=0.70, 95% CI: 0.64-0.77, P <.001, I2=83.8%, Tau2=0.160) studies. The overall analysis concluded that plant-based diets played a protective role in the risk of digestive system neoplasms. Subgroup analyses demonstrated that the plant-based diets reduced the risk of cancers, especially pancreatic (adjusted RR=0.71, 95% CI: 0.59-0.86, P <.001, I2=55.1%, Tau2=0.028), colorectal (adjusted RR=0.76, 95% CI: 0.69-0.83, P <.001, I2=53.4%, Tau2=0.023), rectal (adjusted RR=0.84, 95% CI: 0.78-0.91, P <.001, I2=1.6%, Tau2=0.005) and colon (adjusted RR=0.88, 95% CI: 0.82-0.95, P <.001, I2=0.0%, Tau2=0.000) cancers, in cohort studies. The correlation between vegan and other plant-based diets was compared using Z-tests, and the results showed no difference. Conclusions: Plant-based diets were protective against cancers of the digestive system, with no significant differences between different types of cancer.